HPV Vaccination as Adjuvant to Conization in Women with Cervical Intraepithelial Neoplasia: A Study under Real-Life Conditions - del Pino, Marta (Vaccines (Basel), 2020)
Background: Recent studies have shown preliminary evidence that vaccination against human papillomavirus (HPV) could decrease the risk of persistent/recurrent HSIL in women treated for high-grade cervical intraepithelial lesion (HSIL). We aimed to determine the benefits of HPV vaccination in patients undergoing conization for HSIL in real-life conditions and evaluate vaccination compliance associated with different funding policies. Methods: From January 2013 to July 2018, 265 women underwent conization in our center. From January 2013 to July 2017, treated patients (n = 131) had to pay for the vaccine, whereas after July 2017 the vaccine was publicly funded and free for treated women (n = 134). Post-conization follow-up controls were scheduled every six months with a Pap smear, HPV testing, and a colposcopy. Results: 153 (57.7%) women accepted vaccination (vaccinated group), and 112 (42.3%) refused the vaccine (non-vaccinated group). Persistent/recurrent HSIL was less frequent in vaccinated than in non-vaccinated women (3.3% vs. 10.7%, p = 0.015). HPV vaccination was associated with a reduced risk of persistent/recurrent HSIL (OR 0.2, 95%CI: 0.1–0.7, p = 0.010). Vaccination compliance increased when the vaccine was publicly funded (from 35.9% [47/131] to 79.1% [106/134], p < 0.001). Conclusions: HPV vaccination in women undergoing conization is associated with a 4.5-fold reduction in the risk of persistent/recurrent HSIL. Vaccination policies have an important impact on vaccination compliance.